Classroom intervention to improve behavioral intention toward regular physical activity among adolescents - Jha, Sweety Suman; Dobe, Madhumita; Taklikar, Chandrashekhar; Lahiri, Arista (Frontiers in Public Health, 2024)
Background During adolescence, a critical phase in human life, the groundwork for a healthful future is established. Physical inactivity poses a significant risk factor for non-communicable diseases (NCDs) and related mortality worldwide. To assess adolescents’ behavioral intentions regarding regular physical activity, the Theory of Planned Behavior (TPB) examines ‘Attitude,’ ‘Subjective norm,’ and ‘Perceived behavioral control.’ Utilizing TPB, this study focuses on evaluating the impact of a school-based health promotion intervention on behavioral intentions toward physical activity among urban adolescents in West Bengal, India. Methods A school-based nonrandomized controlled interventional study with parallel group design was conducted among adolescents aged between 12 and 16 years. Behavioral intention towards performing regular physical activity was determined with the measurements of the constructs from the TPB. Cluster analysis was conducted using measurements from both the intervention and control groups. Participants with higher mean scores in the constructs were classified as intenders, while the rest were considered non-intenders. The intervention’s impact was evaluated by calculating the Relative Risk (RR) through a generalized linear model with robust standard error estimates, to ascertain the probability of belonging to the higher intention cluster. Result Following the intervention, construct-wise scores improved significantly, particularly the perceived behavioral control mean score in the intervention group. The Relative Risk (RR) of becoming an intender for regular physical activity in the intervention group was 1.24 (95% CI: 1.04–1.48) when compared to the control group. Conclusion Health Promoting Schools has been recognized as a strategic and cost-effective vehicle to promote positive development and healthful living, and the current evidence suggests they can effectively reduce the emergence of significant NCD risk factor like physical inactivity. Schools must establish strong partnerships with diverse stakeholders to address barriers beyond the school environment and enhance their control over critical issues.